Innovative Strategic Positioning of Capital Flows Mobilization of The Original Five ASEAN Countries: Which are Leading? - Nasution, Eric J.; Krisnawati, Nila (The South East Asian Journal of Management, 2018)
Research Aims - The study was conducted to employ the capital flows mobilization (CFM) indicators as the leading economic indicators to determine the leadership role among the five original ASEAN countries. It sought to simplify and answer three research questions on the differences of CFM indicators among the ASEAN countries, their ranks, and how they were positioned in terms of CFM performance and Granger causality risk level. Methodology - Nonparametric statistics and the economic game theory using a four-quadrant matrix were used to answer the three research questions. Research findings - The first hypothesis was accepted, which indicates that the CFM performance among the five original ASEAN countries differed significantly during the period after the Asian financial crisis in 1998 to 2017. The second research question indicated that Malaysia and Singapore were ranked the first in the ISP of CFM, while Thailand, Indonesia, and Philippines came next to these two leading ASEAN countries. The third research question indicated that Malaysia and Singapore were strategically positioned in the first quadrant, which must deploy the maintenance of highgrowth CFM. Thailand seemed to occupy the innovative CFM refocus strategy, while Indonesia, the expected leading figure in the region, was only positioned fourth. It was expected to fully liberalize and begin with risk diversification in its CFM. The Philippines remained concentrating in its CFM liberalization. Originality - Few studies are considered in the CFM framework, which is integrated with the ISP and using a four-quadrant matrix as an effective measurement. This study is also measuring the ISP effectiveness of CFM in Southeast Asian countries. Managerial implications in the South East Asian Context- The result of the study will be valuable for determining the strategic position of the capital flow mobilization or CFM leading in South East Asian countries. It will enhance the fundamental role of a country in protecting countries from financial turbulences and also on the effectiveness of monetary policy. Research limitations and recommendations - The study focused only on the exploration of how the longitudinal unbalanced panel data of the original ASEAN countries’ economic indicators from the year 2000 to 2016 by utilizing a four-quadrant positioning matrix tool. It is also concentrated only on the former mentioned or money, which flowed in and out of a country’s economic system in accordance with the realm of innovative strategic positioning.